The Power of Integrity of Local Wisdom in Basic Education: Sustainable Development - Andriyanti, Mentari; Suwandayani, Beti Istanti; Amelia, Delora Jantung (Universitas Negeri Padang, 2024)
This study aims to determine the strength of integrity and sustainability of local wisdom in its application in elementary schools. The method used in this research is a systematic literature review that collects various literature or journals. The results of this study show that the integrity of local wisdom in education in elementary schools is one of the essential foundations in shaping students' character, identity, and connection with local culture. Many studies emphasize the values of local wisdom, such as gotong royong, mutual respect, preserving cultural heritage, and teaching the values of perseverance and determination through folklore and traditions. In addition, implementing local wisdom into the learning curriculum is a practical approach and provides significant strength in supporting sustainable development for future generations. Hence, it is essential to cooperate with the government, schools, teachers, and the surrounding community to support the implementation of local wisdom.